Kreasi Mekar Digital : Pemberdayaan Wanita Bethel Indonesia (WBI) Wilayah Manado Melalui Seni Merangkai dan Branding Digital: Kreasi Mekar Digital - Titaley, Jullia; Bobanto, Maria D.; Paendong, Marline S.; Salamena, Allgreat (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
The “Kreasi Mekar Digital” Community Service Program was implemented to enhance woman’s sklls and economic capacity through training in floral arrangement and the strengthening of digital marketing competencies. The ptogram targeted members of the Women of Bethel Indonesia (WBI) in Manado region who have an interest in developing creativity and small craft-based businesses. The activites were carried out ini two main stages : a socialization session on branding and digital marketing strategies and a technical workshop on floral arrangement. This program has had a positive impact on improving participants confidence, digital literacy and entrepreneurial skills. With strong potential for future development, Kreasi Mekar Digital is expected to serve as asustainable community empowerment model that contributes meaningfully to the growth of community-based creative economies. ABSTRAK Program Pengabdian Kreasi Mekar Digital ini dilaksanakan dengan tujuan meningkatkan ketrampilan dan kapasitas ekonomi perempuan melalui pelatihan seni merangkai bunga serta penguatan kemampuan pemasaran digital. Sasaran program adalah anggota Wanita Bethel Indonesia (WBI) wilayah Manado yang memiliki minat dalam pengembangan kreativitas dan usaha kecil berbasis produk kerajinan. Kegiatan dilaksanakn melalui dua tahapan utama yatu sosialisasi materi strategi branding dan pemasaran digital serta pelatihan teknis merangkai bunga.    Program ini memberikan dampak positif dalam meningkatkan kepercayaan diri, literasi digital dan kemampuan wirausaha perempuan WBI. Dengan potens pengembangan di masa depan, Kreasi mekar Digital diharapkan dapat menjadi model pemberdayaan komunitas yang berkelanjutan dan memberikan kontribusi nyata bagi peningkatan ekonomi kreatif berbasis komunitas.